Phenotypic Variation and Carbapenem Resistance Potential in OXA-499-Producing Acinetobacter pittii - Zhang, Linyue; Fu, Ying; Han, Xinhong; Xu, Qingye; Weng, Shanshan; Yan, Biyong; Liu, Lilin; Hua, Xiaoting; Chen, Yan; Yu, Yunsong (Frontiers in Microbiology, 2020)
Acinetobacter pittii is increasingly recognized as a clinically important species. Here, we identified a carbapenem non-resistant A. pittii clinical isolate, A1254, harboring blaOXA-499, blaOXA-826, and blaADC-221. The blaOXA-499 genetic environment in A1254 was identical to that of another OXA-499-producing, but carbapenem-resistant, A. pittii isolate, YMC2010/8/T346, indicating the existence of phenotypic variation among OXA-499-producing A. pittii strains. Under imipenem selective pressure, the A1254 isolate developed resistance to carbapenems in 60 generations. Two carbapenem-resistant mutants (CAB009 and CAB010) with mutations in the blaOXA-499 promoter region were isolated from two independently evolved populations (CAB001 and CAB004). The CAB009 mutant, with a mutation at position −14 (A to G), exhibited a fourfold higher carbapenem MIC and a 4.53 ± 0.19 log2 fold-change higher expression level of blaOXA-499 than the ancestor strain, A1254. The other mutant, CAB010, with a mutation at position −42 (G to A), showed a twofold higher carbapenem MIC and a 1.65 ± 0.25 log2 fold-change higher blaOXA-499 expression level than the ancestor strain. The blaOXA-499 gene and its promoter region were amplified from the wild-type strain and two mutant isolates and then individually cloned into the pYMAb2-Hygr vector and expressed in A. baumannii ATCC 17978, A. pittii LMG 1035, and A. pittii A1254. All the transformed strains were resistant to carbapenem, irrespective of whether they harbored the initial or an evolved promoter sequence, and transformed strains expressing the promoter from the most resistant mutant, CAB009, showed the highest carbapenem MICs, with values of 32–64 μg/mL for imipenem and 128 μg/mL for meropenem. RNA-sequencing was performed to confirm the contribution of blaOXA-499 to the development of carbapenem resistance. Although the CAB009 and CAB010 transcriptional patterns were different, blaOXA-499 was the only differentially expressed gene shared by the two mutants. Our results indicate that carbapenem non-resistant Acinetobacter spp. strains carrying blaOXA genes have the potential to develop carbapenem resistance and need to be further investigated and monitored to prevent treatment failure due to the development of resistance.